Perlindungan Hukum Terhadap Korban Politik Identitas - Achmad Mujadid Salim (Faculty of Law, Universitas Airlangga, 2022)
AbstractIndonesia is a multicultural country characterized by its diverse ethnicities, tribes and religions. Laws be it national and international have been regulating the protection of human rights, including the right to be recognized as an individual, right of equality before the law, religious rights, as well as the right to participate in government. Identity politics has made the rights of minorities less significant as discrimination against individuals or groups coming from minority class with different background exists. The plurality of society (plures) cannot be eliminated for the sake of the jargon of unity (unum), because unity must be achieved through the existence of plurality. Facts in various cases, the element of religious pluralism is often accused as a trigger factor or even the cause of social conflict and collective violence. This accusation is certainly not entirely wrong, because not a few people who use religion as justification in achieving political goals and interests. The result of this research shows the existence of human rights violations caused by identity politics.Keywords: Human Rights; Identity Politics; Discrimination. AbstrakIndonesia merupakan negara yang Multikuktur, keberagaman etnis, suku dan agama merupakan ciri dari bangsa ini.Peraturan nasional maupun internasional telah mengatur perlindungan terhadap hak asasi manusia yang termasuk didalamnya menjamin hak untuk diakui sebagai pribadi dan persamaan di hadapan hukum, hak beragama dan hak turut serta dalam pemerintahan. Politik Identitas membuat orang yang berasal dari kelompok minoritas dikurangi hak-nya karena perbedaan latar belakang identitas yang menyebabkan diskriminatif terhadap kelompok atau perseorangan yang berasal dari golongan minoritas. Kemajemukan masyarakat (plures) tidak dapat dilenyapkan demi jargon persatuan (unum), sebab persatuan itu harus dicapai lewat keberadaan pluralitas. Fakta dalam berbagai kasus, unsur kemajemukan agama seringkali dituduh sebagai faktor pemicu atau bahkan penyebab terjadinya konflik sosial dan kekerasan kolektif. Tuduhan ini tentu tidak sepenuhnya salah, karena tidak sedikit kalangan yang menggunakan agama sebagai justifikasi dalam mencapai tujuan dan kepentingan politik. Hasil penelitian ini menunjukkan bahwa adanya pelanggaran hak asasi manusia yang disebabkan oleh politik identitasKata Kunci: Hak Asasi Manusia; Politik Identitas; Diskriminasi.